2008
DOI: 10.1111/j.1399-6576.2008.01634.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative dreams reported after general anaesthesia are not early interpretations of delayed awareness

Abstract: We found a statistically significant association between dreams reported after general anaesthesia and awareness, although intraoperative dreams were not an early interpretation of delayed awareness in any case. A typical dreamer in this study is a lean female having a short procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
3
18
0
Order By: Relevance
“…Some researchers believed that intra-operative awareness is more likely to occur with intravenous agents, [23][24][25] but there were also contrasting opinions. 26 The statistical results of this investigation showed that the method of anesthesia (TIVA, inhalation anesthesia, balanced anesthesia, general anesthesia combined with nerve blockage) was definitely a relevant factor (OR 5 0.525, 95% CI: 0.392-0.703, for TIVA compared with inhalation anesthesia and balanced anesthesia; P 5 0.001) of intra-operative awareness. This suggested that intravenous or inhaled anesthetics indeed affected the presence of intra-operative awareness.…”
Section: Discussionmentioning
confidence: 70%
“…Some researchers believed that intra-operative awareness is more likely to occur with intravenous agents, [23][24][25] but there were also contrasting opinions. 26 The statistical results of this investigation showed that the method of anesthesia (TIVA, inhalation anesthesia, balanced anesthesia, general anesthesia combined with nerve blockage) was definitely a relevant factor (OR 5 0.525, 95% CI: 0.392-0.703, for TIVA compared with inhalation anesthesia and balanced anesthesia; P 5 0.001) of intra-operative awareness. This suggested that intravenous or inhaled anesthetics indeed affected the presence of intra-operative awareness.…”
Section: Discussionmentioning
confidence: 70%
“…The described patient who had an episode of intraoperative awareness reported no dreams under general anesthesia. In our study, intraoperative dreaming was included in a separate category, not related to intraoperative awareness 7,60,61 ; however, some authors believe that their occurrence may result from inadequate level of anesthesia 59 . Our results are both interesting and clinically useful.…”
Section: Discussionmentioning
confidence: 99%
“…This corresponds with the literature, where the incidence of dreaming during general anesthesia varies between 1% and 22% (ref. 7,59,60 ). The described patient who had an episode of intraoperative awareness reported no dreams under general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…A level of general anesthesia appropriate for surgery is not sleep but rather a coma (Brown et al 2010). However, like sleep, general anesthesia is reversible and can allow dreaming (Leslie & Skrzypek 2007, Errando et al 2008, Samuelsson et al 2008). The concept of coma is less comforting and harder for patients to understand than the notion of sleep.…”
Section: Implications and Future Directionsmentioning
confidence: 99%